Corrosion and passivation behavior of laser powder bed fusion produced Ti-6Al-4V in static/dynamic NaCl solutions with different concentrations. (October 2021) - Qin, P.; Chen, L.Y.; Liu, Y.J.; Jia, Z.; Liang, S.X.; Zhao, C.H.; Sun, H.; Zhang, L.C.
Highlights: SLMed Ti6Al4V was tested in static/dynamic NaCl solutions with different concentrations. The formed oxide film on SLMed Ti-6Al-4V includes TiO2, Ti2 O3 and TiO. The overall film thickness enhances with the increase in the Cl − concentration. The film formed in dynamic conditions contains more defects. The better corrosion resistance of the sample tested in static conditions was found. Abstract: In this work, the corrosion and passivation behavior of Ti-6Al-4V produced by laser powder bed fusion (L-PBF) were investigated in different concentration of NaCl solutions under static and dynamic conditions. Oxide films including TiO2, Ti2 O3, TiO were formed on L-PBF-produced Ti-6Al-4V. The film thickness increased under both test conditions with increasing the Cl − concentration, and the film contained more TiO2 in dynamic conditions under the same Cl − concentration. The mechanism of the corrosion behavior and film growth under different Cl − concentration and electrolyte conditions were discussed by the relevant electrochemical and surface characteristic measurements, e.g. Mott-Schottky analysis, X-ray photoelectron spectroscopy.